Assessing Skin Healing and Angiogenesis of Deep Burns in Vivo Using Two-Photon Microscopy in Mice - He, Gaiying; Cao, Yu; Tang, Jinghui; Ma, Shuhua; Sun, Yanan; Yang, Weifeng; Tong, Qian; Li, Dongying; Wang, Yi (Frontiers in Physics, 2022)
Prevalent methods for monitoring burn injuries and testing drug efficacy rely on fixed tissue sections. However, this may leave out cellular details in the living state. In vivo assessment of burn healing has been long sought and are of scientific and clinical interest. Nicotinamide adenine dinucleotide (phosphate) (NAD(P)H), collagen, melanin are endogenous fluorescent molecules and their signals can be captured by Two-photon microscopy (TPM), therefore providing information on epidermal histological features and collagen growth in real-time. In addition, TMP imaging on exogenous fluorescent substances provides basis for detecting blood vessels. In this work, TPM was used to capture the exogenous fluorescent substances and endogenous fluorescent molecules at different times to assess and track burn healing in vivo. Combining TPM imaging and morphological characteristics, proliferation and differentiation of the keratinocytes in different layers of skin, collagen contents and angiogenesis were identified and quantified. TPM monitoring method provides an effective tool to systemically evaluate skin healing of deep burns in vivo.